2014
DOI: 10.1038/ncomms5545
|View full text |Cite
|
Sign up to set email alerts
|

Ionic field effect and memristive phenomena in single-point ferroelectric domain switching

Abstract: Electric field-induced polarization switching underpins most functional applications of ferroelectric materials in information technology, materials science and optoelectronics. Recently, much attention has been focused on the switching of individual domains using scanning probe microscopy. The classical picture of tip-induced switching, including formation of cylindrical domains with size, is largely determined by the field distribution and domain wall motion kinetics. The polarization screening is recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 46 publications
2
52
0
Order By: Relevance
“…back switching [80][81][82][83][84] and chaotic screening of ferroelectrics by PFM. 85,86 However, these studies demonstrated that KPFM (or any other long-range field contrast) is controlled by the interplay between polarization and (poorly understood and controlled) screening and charging processes, and does not provide information on ferroelectric behavior per se. Furthermore, the spatial resolution of KPFM is limited to ~50 nm, above the range of interest for ferroelectric materials often containing nanometer-scale domain structures.…”
Section: Iia Basic Pfmmentioning
confidence: 99%
See 1 more Smart Citation
“…back switching [80][81][82][83][84] and chaotic screening of ferroelectrics by PFM. 85,86 However, these studies demonstrated that KPFM (or any other long-range field contrast) is controlled by the interplay between polarization and (poorly understood and controlled) screening and charging processes, and does not provide information on ferroelectric behavior per se. Furthermore, the spatial resolution of KPFM is limited to ~50 nm, above the range of interest for ferroelectric materials often containing nanometer-scale domain structures.…”
Section: Iia Basic Pfmmentioning
confidence: 99%
“…For polarization, the underpinning phenomena are similar, except that regions with switched polarization play the role of a virtual electrode. The accumulation, injection, and transport of ionic charge now becomes an inherent part of the switching process, as illustrated by phenomena such as the formation of bubble domains during back switching, 80,242 domain shape stability loss, 85 and chaos 86 during ferroelectric switching.…”
Section: A Surface Ionic Screeningmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Abnormal switching behaviors, including backswitching, 12,15,[21][22][23] polarization reversal by the "wrong" polarity of the switching voltage 7,11,17,19 and switching along the path of the unbiased SPM tip 18, 24 were reported. These phenomena were attributed to the charge injection 12,15 , screening of the applied electric fields 25 and ferroelastoelectric switching.…”
mentioning
confidence: 99%
“…In the case of switching against applied electric field, 12,15,19 electric field induces in the tip are due to the injection of the screening charges near the tip. In the case of backswitching with formation of the ring-shaped domains, 18,[21][22][23] this is due to charges on the charged domain walls of the non-through domain.…”
mentioning
confidence: 99%
“…This technique consists of application the local electric field and visualization of the created domains with nanometer spatial resolution. A large amount of papers are devoted to the investigation of the local polarization reversal in various ferroelectrics, such as lithium niobate [2][3][4], but domain kinetics in relaxors is still insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%